(untitled) (Research, Society and Development, 2022)
This work aims to carry out a case study on the municipal council for sustainable rural development (CMDRS) of the municipality of Tangará da Serra-MT. The implantation process, motivation, functioning format and structure were analyzed. Management of this Council, together with the guidelines over the years. For the basis of this study, a literature review was built on the CMDRS in Brazil, with researches on articles, laws and websites, as well as consultation with the internal rules of the respective Council, which allowed to develop a detailed history About the process of creating these spaces and their activities. The CMDRS of the municipality is in effect and has undergone many changes in its composition and structuring since its creation until today not being very clear some of these modifications. The main guidelines dealt with in the meetings revolve around, structuring of the PRONAF, structuring of the CMDRS, agricultural patrols, land credit and technical chambers. The minutes studied allowed to verify the functionality of the CMDRS of Tangará da Serra, being visible that despite having limitations as well as in several other councils, this in effect and fulfilling its role as mediator between family farmers and entities Which may in some way contribute to the sector.